Investigation The Relationship Of Emotional Intelligence (EI) And Organizational Citizenship Behaviour (OCB) In Malaysian Organizations - Dehghan, Mostafa (2011)
This present study examines the efficacy of EI clusters, in predicting OCB. The research is designed to specifically examine the relative contribution of every emotional intelligence cluster to OCB, focusing on employees working in different corporations and firms in the city of Kuala Lumpur.